HUBUNGAN KEMAMPUAN MENYELESAIKAN TUGAS-TUGAS PELAJARAN DENGAN HASIL BELAJAR SISWA - Suryadi Suryadi; Erlamsyah Erlamsyah; Yusri Yusri (Jurnal EDUCATIO: Jurnal Pendidikan Indonesia, 2016)
Student learning outcomes are influenced by the ability to complete the learning task. Phenomena in the field most of the students are not able to complete the task given lesson. This study aims to reveal how the relationship between the ability to complete the task of learning to students' learning outcomes. This study uses quantitative type of correlational research. The study population was a junior high school UNP (Padang State University) Development Laboratory by the number of students 384 people. Sample is proportional random sampling by the number of students 78. There is a significant relationship between the ability to complete the task of learning to students' learning outcomes.